2016
DOI: 10.1111/os.12234
|View full text |Cite
|
Sign up to set email alerts
|

En Bloc Resection of Primary Malignant Bone Tumor in the Cervical Spine Based on 3‐Dimensional Printing Technology

Abstract: Though technically challenging, it is feasible and safe to perform en bloc resection of cervical primary bone tumors. This is the most effective means of managing cervical spine tumors. Preoperative 3-D printing modelling enables better anatomical understanding of the relationship between the tumor and cervical spine and can assist in planning the surgical procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 44 publications
0
37
0
4
Order By: Relevance
“…It is a readily available and inexpensive method. 3D printing have been applied in several studies, which is used for preoperative observation and individualized preoperative design, in treating upper cervical diseases [9] and spinal tumors [10]. We supposed that 3D printing technique could improve the accuracy of bare-hands screw placement and reduce empirical errors.…”
Section: Introductionmentioning
confidence: 99%
“…It is a readily available and inexpensive method. 3D printing have been applied in several studies, which is used for preoperative observation and individualized preoperative design, in treating upper cervical diseases [9] and spinal tumors [10]. We supposed that 3D printing technique could improve the accuracy of bare-hands screw placement and reduce empirical errors.…”
Section: Introductionmentioning
confidence: 99%
“…10 Recently, several navigation template systems for high cervical spine were reported. [21][22][23][24][25][26][27] Although lack large comparative study, accuracy of cervical pedicle screw insertion using guiding template showed no inferior to previous methods. 10 3D-printed personalized guiding template has advantage in addition to accuracy, such as less radiation exposure, lower operation time, and shorter learning curve.…”
Section: Discussionmentioning
confidence: 99%
“…With development and innovation of the technology driving down costs, the use of 3Dp has become more widespread, eventually resulting in United States Food and Drug Administration approval for several 3Dp devices (Lee, 2016). As described above, 3Dp has many advantages for surgical usage and has become particularly popular in orthopaedic, maxillofacial, cranial and spinal surgery (Guenette et al, 2016;Liew et al, 2015;Onerci Altunay et al, 2016;Schwam et al, 2016;Tack et al, 2016;Wiedermann, et al, 2017;Xiao et al, 2016;Yang et al, 2016), whilst a growing number of case studies have described its use in fields such as interventional radiology (Ghisiawan, et al, 2017;Hossien et al, 2016;Kurup et al, 2015;Schmauss et al, 2015;Shi, et al, 2015;Sodian et al, 2009), paediatric surgery (Morrison et al, 2015;Schmauss et al, 2015) and oncological surgery (Al Jabbari et al, 2016;Bernhard et al, 2016;Matsumoto et al, 2016). To date, 3Dp models have been used primarily as surgical guides and for pre-operative surgical planning (Tack et al, 2016).…”
Section: Medical Usagementioning
confidence: 99%
“…Using a 3Dp model as a navigational guide can allow surgeons to proceed more safely. A safe resection margin during an en-bloc cervical spondylectomy for a primary malignant bone tumor has been planned, identifying which neurovascular structures must be sacrificed or could be avoided (Xiao et al, 2016). In some cases, the pre-operative identification of tumor borders resulted in a smaller incision and less invasive approach, factors that could impact upon recovery (Al Jabbari et al, 2016;Matsumoto et al, 2016).…”
Section: Medical Usagementioning
confidence: 99%